A reassessment of the risk of rust fungi developing resistance to fungicides - Oliver, Richard (John Wiley & Sons Ltd., 2014)
Rust fungi are major pathogens of many annual and perennial crops. Crop protection is largely based on genetic and chemical control. Fungicide resistance is a significant issue that has affected many crop pathogens. Some pathogens have rapidly developed resistance and hence are regarded as high-risk species. Rust fungi have been classified as being low risk, in spite of sharing many relevant features with high-risk pathogens. An examination of the evidence suggests that rust fungi may be wrongly classified as low risk. Of the nine classes of fungicide to which resistance has developed, six are inactive against rusts. The three remaining classes are quinone outside inhibitors (QoIs), demethylation inhibitors (DMIs) and succinate dehydrogenase inhibitors (SDHIs). QoIs have been protected by a recently discovered intron that renders resistant mutants unviable. Low levels of resistance have developed to DMIs, but with limited field significance. Older SDHI fungicides were inactive against rusts. Some of the SDHIs introduced since 2003 are active against rusts, so it may be that insufficient time has elapsed for resistance to develop, especially as SDHIs are generally sold in mixtures with other actives. It would therefore seem prudent to increase the level of vigilance for possible cases of resistance to established and new fungicides in rusts.